Ultrasonography Profiles in Patients with Asymptomatic Hyperuricemia - Awalia, -
SUMMARYBackgrounds: Asymptomatic hyperuricemia (AHU) patients mostly do not develop gouty arthritis. The best procedure to investigate whether they have MSU deposition has not been established. We report our preliminary study about ultrasonography on AHU patients.Methods: In this cross-sectional study, we enrolled asymptomatic hyperuricemia patients who matched the gout classification criteria of the American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) (2015). Six joints were examined per patient by ultrasonography including the first metacarpophalangeal (MCP) joints, first metatarsophalangeal (MTP) joints, and trochlear knees to determine pathological findings which may demonstrate clinically silent urate deposits in asymptomatic hyperuricemia individuals. Results: Average age was 49.27±12.35 years old. The average serum uric acid level was 7.64±1.67 mg/dL. Ultrasonography of the first MCP showed joint effusion in 11 patients (73 %), double contour in 10 patients (66 %), tophus in 1 patient (6 %), snowstorm appearance in 1 patient, hypervascularization in 1 patient, and synovitis in 3 patients (20 %). Four patients revealed normal features. First MTP joints showed 13 joint effusions (86 %), double contours in 13 patients (86 %), 1 bone erosion (6 %), 3 tophi (20 %), and 2 synovitis (13 %). There was no hypervascularization or snowstorm appearance found. Two patients showed normal USG. From trochlear knees, we found 1 joint effusion (6 %), and 1 double contour (6 %), and 14 patients were normal. Conclusions: Abnormal ultrasound findings such as double contour sign and tophi were detected in asymptomatic hyperuricemia. The most frequent joint affected was the first MTP. Whether this result influences our decision to initiate urate-lowering therapy and anti-inflammatory treatment is still to be determined.